THE EFFECT OF ADDING COLD-STANDBY REDUNDANCY ON THE INCREASE OF SYSTEM RELIABILITY - Kadhem, Alia’a (Iraqi Journal of Science, 2024)
In this research, we study the effect of adding cold-standby redundancy inincreasing system reliability. Cold-standby redundancy is essential in the study ofmaintenance polices.